Effect of balanced energy-protein supplementation during pregnancy and lactation on birth outcomes and infant growth in rural Burkina Faso: Study protocol for a randomised controlled trial - Vanslambrouck, Katrien; de Kok, Brenda; Toe, Laeticia Celine; De Cock, Nathalie; Ouédraogo, Moctar; Huybregts, Lieven (BMJ, 2021)
Adequate nutrition during pregnancy is crucial to both mother and child. Maternal malnutrition can be the cause of stillbirth or lead to poor birth outcomes such as preterm delivery and small-for-gestational-age newborns. There is a probable positive effect of providing pregnant women a balanced energy-protein (BEP) food supplement, but more evidence is needed. The MIcronutriments pour la SAnté de la Mère et de l’Enfant (MISAME) III project aims to improve birth outcomes and infant growth by testing a BEP supplement during pregnancy and lactation in rural Burkina Faso. This paper describes the study protocol.